FEASIBILITY STUDY OF SUDUT GROUPâS HOTEL AND RESTAURANT BUSINESS AT PANTAI INDAH KAPUK 2 - Christopher Wirja, Daniel
The hospitality sector is crucial to Indonesia's economy, especially in cities like Jakarta, Bandung, and Surabaya. Sudut Group, with its successful ventures in Bandung, plans to expand into Pantai Indah Kapuk 2 (PIK 2) in Jakarta. This study evaluates the economic feasibility of this new project.